Influence of Counselling Services on Academic Performance of Students in Public Senior Secondary Schools in Plateau State - Gobring Nensok Nenmane; Zainab Ibrahim Sulaiman; Vincent Augustine Buoro; Umar Muhammad Salisu (Current Educational Review, 2026)
This study investigates the influence of counselling services on the academic performance of students in public senior secondary schools in Plateau State, Nigeria. The research was driven by the increasing recognition of counselling as a crucial intervention for addressing students’ academic, psychological, and social challenges, thereby fostering better educational outcomes. Specifically, the study investigated the influence of four key categories of counselling services; preventive, crisis, rehabilitative, and referral on students’ academic performance. Using a descriptive survey research design, the researcher collected data from a sample of 370 students selected through random sampling from fifteen public senior secondary schools in Plateau State. Out of these, 353 valid responses were analyzed using both descriptive statistics and inferential techniques, including multiple regression analysis, to determine the strength and significance of the relationships between counselling services and academic performance. The hypothesis testing revealed that all four categories of counselling services had a statistically significant positive effect on students’ academic performance (p < 0.05). Specifically, referral counselling services exhibited the strongest influence with a standardized beta coefficient (β) of 0.45 (p < 0.01), indicating that increased access to referral services could substantially improve academic outcomes. Rehabilitative counselling followed with a β of 0.32 (p < 0.01), suggesting that rehabilitative support plays a vital role in enhancing academic success. Crisis counselling also demonstrated a significant impact with a β of 0.28 (p < 0.05), while preventive counselling showed a positive but comparatively modest effect (β = 0.21, p < 0.05). The results suggest that targeted interventions, especially referral and rehabilitative services, are instrumental in addressing students’ individual needs and promoting academic performance. The study concludes that the effective implementation of well-structured counselling programs, supported by qualified counsellors and adequate resources, is essential for improving educational outcomes. The study therefore recommends that government and educational authorities prioritize the expansion and strengthening of counselling services in secondary schools. This includes employing trained personnel, providing necessary facilities, and increasing awareness among students about the availability and benefits of counselling, thereby fostering not only improved academic performance but also supporting students’ overall psychological and social well-being